Impact of soil organic matter on groundwater contamination risks for ethanol and butanol blended gasoline - Ugwoha, Ejikeme (2013)
This work examined the impact of soil organic matter (SOM) on the sorption, phase distribution and transport of ethanol and butanol blended gasoline vapours after release. Microcosm and mini-lysimeter experiments were conducted using sand with varying SOM and moisture contents. Synthetic gasoline alone and blended with 10 - 20% ethanol and 10 - 20% butanol by volume, referred to as UG, E10 - E20 and B10 - B20, respectively, were used. Results from the UG were used as the benchmark to assess the impact of ethanol and butanol on gasoline compounds. The findings of this work illustrate the likely behaviour of gasoline compounds at the beginning times of a gasoline spill or leak.